Pulsed electrodeposition of p-type CuInSe2 thin films - Valdes, Matias Hernan (2011)
CuInSe2 thin films have been electrodeposited on conductive glass using cyclic pulse electrodeposition. One cycle consists of consequtively applying potentials E1 and E2, each during 10 s and a total of 90 cycles are applied. E1 is chosen between -0.7 and -0.9 VSCE while E2 is fixed at -0.1 VSCE. The films are annealed in argon and then etched in KCN solution to eliminate remnant secondary phases. The material is characterized employing grazing incident X-rays diffraction, Raman spectroscopy, scanning electron microscopy and energy dispersive scanning spectroscopy. The presence of secondary phases seems to be reduced when compared to films prepared at fixed potentials. The films are crystalline and the overall quality improves by annealing in Ar. Photoelectrochemical tests, Mott-Schottky plots and I-V curves confirm p-type conduction. The diffusion regime imposed by the potential pulses could be responsible for the different morphology and composition of samples prepared with pulsed and potentiostatic electrodeposition.